Analisis Daya Saing Ekspor Cengkih Indonesia dan Madagaskar di India Tahun 2012-2021 - Renaldi, Eddy; Noor, Trisna Insan; Pardian, Pandi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Indonesia and Madagascar are world clove exporting countries, with India as the leading export destination and having quite a high demand.   This research aims to comparatively analyze the competitiveness of Indonesian and Madagascar cloves in the Indian market using the Revealed Comparative Advantage (RCA) analysis tool, and the relationship between export value and volume to RCA is calculated using the Pearson product-moment correlation analysis technique 2012-2021. Research results show that the average RCA value for Indonesia is more excellent, 4.29, compared to Madagascar's 2.31, in 2012-2021, so cloves from Indonesia are more competitive than Madagascar cloves in India. The volume and value of clove exports to India from 2012 to 2021 had a strong and significant effect on the RCA value in Indonesia, while in Madagascar, it had no effect on the RCA value or a negative relation and was not significant.